Synthesis and Characterization of ZnO Nanoparticles using the Duwet (Syzygium cumini) Leaves Extract as Bioreductor - Evawati, Kholif; Sutoyo, Suyatno (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
The synthesis of ZnO nanoparticles was conducted using a green synthesis method that utilizes plants as bioreductors. The secondary metabolites contained in the plants can act as bioreductors in the reduction process of metal oxides and as capping agents in the production of ZnO nanoparticles. This research aims to determine the characterization of ZnO nanoparticles using Syzygium cumini leaves extract as bioreductor. The type of research is experimental research. In this study, the characteristics of ZnO nanoparticles were examined using extracts from the leaves of the duwet tree (Syzygium cumini). Synthesis was performed with varying compositions of zinc acetate dihydrate solution and duwet leaf extract at ratios of 1:1, 1:2, 1:3, and 1:4, as well as pH levels of 7, 8, 9, and 10. The nanoparticles were then characterized using UV-Vis spectrophotometry and a Particle Size Analyzer (PSA) to determine the optimal conditions. The optimal conditions for synthesizing ZnO nanoparticles were obtained with a maximum wavelength (λmax) of 368 nm at a ratio of 1:2 and pH 8. The particle size distribution analysis from the PSA indicated an average size of 19.52 nm, with a Poly Dispersity Index (PDI) value of 0.2491. The analysis results using XRD showed the synthesized nanoparticles showed the typical peak for ZnO with 2θ values of 31,7680o, 34,3699 o, and 36,2281o, confirming that the synthesis of nanoparticles had successfully produced ZnO nanoparticles. The UV-Vis, FTIR, and XRD characterization results showed that the nanoparticles produced were pure ZnO nanoparticles.